Potential for coronary CT angiography to tailor medical therapy beyond preventive guideline-based recommendations: Insights from the ROMICAT I trial - Pursnani, Amit; Schlett, Christopher L. (Journal of cardiovascular computed tomography, 2015)
Coronary CT angiography (CCTA) is used in the emergency department to rule out acute coronary syndrome in low-intermediate risk patients. We evaluated the potential of CCTA to tailor aspirin (ASA) and statin therapy in acute chest pain patients. We included all patients in the ROMICAT I trial who underwent CCTA before admission. Results of CCTA were blinded to caretakers. We documented ASA and statin therapy at admission and discharge and determined change in medications during hospitalization, agreement of discharge medications with contemporaneous guidelines, and agreement with the presence and severity of coronary artery disease (CAD) as determined by CCTA. We included 368 patients (53 ± 12 years; 61% male). Baseline medical therapy at presentation included 27% on ASA and 24% on statin. Most patients who qualified for secondary prevention were on ASA and statin therapy at discharge (95% and 80%, respectively), whereas among those qualifying for primary prevention therapy, only 59% of patients were on aspirin and 33% were on statin at discharge. Excluding secondary prevention patients, among those with CCTA-detected CAD, only 66/131 (50%) were on ASA at discharge and only 53/131 (40%) were on statin. Conversely, in those without CCTA-detected CAD, 54/156 (35%) were on ASA and 20/151 (13%) were on statin at discharge. There are significant discrepancies between discharge prescription of statin and ASA with the presence and extent of CAD. CCTA presents an efficient opportunity to tailor medical therapy to CAD in patients undergoing CCTA as part of their acute chest pain evaluation.
Gesehen am 16.08.2017